Formação continuada dos professores de educação física da rede pública de ensino no município de Aracaju : mediações do "Programa Horas de Estudo" - Lira, Núbia Josania Paes de (2015)
This research has the object of study Continuing Education of Physical Education Teachers in Municipal network Aracaju Teaching from the "Hours of Study Programme", whose scientific research focuses on the relationship content and present in the development of Appreciation and Training teachers and the educational labor Organization, as important prerequisites for qualification of educational work. This study was part of the set of scientific contributions developed by the Group of Studies and Research in Physical Education & Sport and leisure- GEPEL on line search Teacher Training and Teaching Work articulated the LEPEL network. It presented as scientific relevance diagnosis on the Continuing Education of Teachers of Physical Education, with emphasis on the trajectory of the teaching profession in the 1986- 2012 period, making an analysis of 26 years of work in order to understand the reality and possibilities of Continuing Education Teachers. The general objective is to analyze the connections and relationships in the educational policy of "Time Studies Program" aimed at continuing education of teachers and the production of the Pedagogical Work Organization of Physical Education teachers of Basic Education in the Municipal Network of Education of Aracaju / SE . And the following objectives: a) to analyze the contributions of Continuing Teacher Education considering the discussion of public policy proposals and theoretical productions with its reach in the Municipal network Aracaju Education identifying the influence of Education of commercialization in the capital of the company; b) verify and explain the reality of Physical Education in the Municipal network Aracaju Education articulated the Continuing Education Policy Teachers through the "Hours of Study Programme" seeking to prove the concept of continuing education and identify links with the organization of the pedagogical work c) contribute to the continuing education proposal mediated by the categories of teaching practice of physical education teacher of the Municipal network of Aracaju Education from the point of view of socially useful work beyond the capital. From a methodological point of view, we opted for the historical dialectic materialism, considering two fields categorical interlocking for the appropriation of the laws of the internal dynamics of the research problem, articulating the theoretical categories Reality and Possibilities from Cheptulin (1982) and the categories of content involving Epistemological Bases, Pedagogical bases and Structural basis for the diagnosis of the investigation. The composition of the diagnosis of reality is done by collecting data from interviews with teachers in retirement process (25 year career), physical education coordinator SEMED and secretary of education in the municipal and documentary analysis of theoretical materials methodological produced in the process of continuing education, the SEMED site and SINDIPEMA advertising material. The possibilities for continuing education in Aracaju Municipal Education network link to the implementation of a policy of upgrading and professionalization of teachers articulated to the country's educational project in addressing existing social problems, expressed in a comprehensive and continuous training policy with conditions job, salary and career.